Factors influencing decision to seek health care: a qualitative study among labour-migrants’ wives in northern Tajikistan - Nabieva, Jamila; Souares-Coutant, Aurélia (BMC pregnancy and childbirth, 2019)
This qualitative study aimed to investigate the health seeking behaviour of rural women in northern Tajikistan, with specific focus on antenatal and obstetric complications as a result of delayed access to health services. Due to the unprecedented level of labour migration among men in the border region of Tajikistan, Isfara, the study specifically focused on migrants’ wives residing with their in-laws.